REIMAJINASI POLITIK DALAM NOVEL RABET, RUNTUHNYA JERMAN TIMUR KARYA MARTIN JANKOWSKI - Akhmad Taufiq (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to describe the factors, ideological reconstruction process, and political reimagination process in a nationhood phenomenon of the reunification of Germany as anation and a state. The data source was Rabet, Runtuhnya Jerman Timur, a novel by MartinJankowski. The study employed the perspective of new historicism studies through threesteps of analysis, namely the ideological dimension, discursive practice at the time theevents occurred, and discursive practice in the present context. The results of the studysuggest that the reunification of Germany as a nation is based on three factors, namely: (1) the presence of collective consciousness among the citizens of East Germany and WestGermany to live together after they have lived apart for decades; (2) the awareness of theimportance of ideological reconstruction for the country to be built, that is the presence ofalternative political ideology in the third way; and (3) the political reimagination drivenby racial dimension awareness enabling freedom to grow, violent acts to disappear, andwelfare to be realized as envisioned ideals.